2014
DOI: 10.5772/59027
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Manufacturing Operations through a Lean Management Approach: A Case Study in the Pharmaceutical Industry

Abstract: This paper aims to demonstrate the positive effect of a Lean Management (LM) approach to increasing efficiency, even in a company which is subject to critical market issues. The pharmaceutical industry is a well-known example of a crisis-affected context and companies have directed attention to Lean Management for a long time, but they are stable in increasing effectiveness. This research uses a case study to move the attention to efficiency as an attractive LM goal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
2
20
0
2
Order By: Relevance
“…The majority of the participating firms have already implemented LM, partially or fully, and therefore they may have been expected to already have adequately developed their quality practices. The literature is full of references of LM in the pharmaceutical industry (Nenni et al, 2014), and also of successful lean stories for large pharmaceutical manufacturers such as Lunbeck (Houborg, 2010), GSK (Carleysmith et al, 2009), Novo Nordisk, Novartis and Abbott pharmaceuticals (Friedli et al, 2013), all of which reported remarkable improvements in their manufacturing operations. Thus, keeping in view the significant amount of time that an operational excellence approach such as LM requires for its full deployment (Friedli et al, 2013), the results obtained from this research may be explained based on the assumption that the participant organisations were in the early stages of the LM implementation.…”
Section: Rq1 Are European Pharmaceutical Manufacturers Capable Of Sumentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the participating firms have already implemented LM, partially or fully, and therefore they may have been expected to already have adequately developed their quality practices. The literature is full of references of LM in the pharmaceutical industry (Nenni et al, 2014), and also of successful lean stories for large pharmaceutical manufacturers such as Lunbeck (Houborg, 2010), GSK (Carleysmith et al, 2009), Novo Nordisk, Novartis and Abbott pharmaceuticals (Friedli et al, 2013), all of which reported remarkable improvements in their manufacturing operations. Thus, keeping in view the significant amount of time that an operational excellence approach such as LM requires for its full deployment (Friedli et al, 2013), the results obtained from this research may be explained based on the assumption that the participant organisations were in the early stages of the LM implementation.…”
Section: Rq1 Are European Pharmaceutical Manufacturers Capable Of Sumentioning
confidence: 99%
“…The European pharmaceutical industry is considered a valuable asset of the European economy, with the best performing ratio among all other industries in the continent, and with a 25 percent value of the overall global pharmaceutical industry (Nenni et al, 2014). However, this industry has been facing important challenges related to the increase of R&D costs, decline in efficiency, expiration of numerous patents (Nenni et al, 2014), which has resulted is a considerable drop in profits (Friedli et al, 2013). As a result, an imperative need for improving their operational performance through the adoption of process excellence programmes such as the lean approach has emerged as an opportunity to address these challenges (Wagner et al, 2009;Friedli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lean manufacturing was developed for maximum utilization of the resource and reducing the waste [1] Lean manufacturing widely used in the industry to increase the productivity without additional resource [2] Due to fast change in the market industry is forced to face the challenges to produce low volume high variant products [3] To implement the lean in assy line need to do activities like analyzing the layout, batch size and process follow to increase overall equipment effectiveness [4] Designing facility in order to flexible, modularity and scalable responsive to manufacturing system to accommodate dynamic changes of product variant [5] lean manufacturing principles involves reducing the cost by identifying the value added and non-value added activity [6] Lean manufacturing is used to fill the current gap in proper innovative approach to measure the lean performance manufacturing system [7] Lean manufacturing is used to demonstrate positive effect approach to increase efficiency when crises occurred. [8] Lean as a long term philosophy about the right process which is used produce a right product by adding value to the organization [9] value stream mapping is the main tool is used to identify the opportunities for the various lean techniques, which used discrete manufacturing rather than the continuous manufacturing [10] Elimination non value added activities and increasing the value added activities which directly increases the plant performance.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, one of the methodologies that has shown to be successful is the lean manufacturing, where tools are used, such as: Kaizen, Kanban, Single-minute Exchange of Dies (SMED), Six Sigma, Value Stream Mapping (VSM), 5'S, Total Quality Management (TQM), Theory of Constraints, Total Productive Maintenance, Administration Visual, Poka Yoke, etc. to maximize the value string [1,2]. The procedure of Lean Manufacturing is to select a product (or family) and study the process of manufacturing, using diagrams of operations, flow, travel and build a map of the current value chain (VSM) to identify waste; according to the type of waste, the appropriate tool is selected to eliminate or decrease it.…”
Section: Introductionmentioning
confidence: 99%